Assassination in colonial Cyprus in 1934 and the origins of EOKA reading the archives against the grain - Varnava, Andrekos 1979- (Anthem studies in British history, 2021)
After a long and hard day at work, which had taken him to Larnaca, Antonios Triantafyllides, a leading lawyer recently appointed to the Cypriot government's Advisory Council, arrived at his Nicosia home in the cool evening of 12 January 1934, only to be shot by an unknown assailant. He died the next morning. Twelve months later, Stavros Christodoulou was charged, but acquitted of the murder. Considered political, the murder has been a taboo subject for Cypriot society and historians alike, and a cold case that nobody has seemingly taken any interest in solving let alone in exploring (at least publicly), that is, until now. This book offers a theory on who was behind the assassination, the first attempt to explain an 87-year-old cold case. In doing so, it explores both the relationship between the British colonial authorities and the Cypriot political elites, and the various divisions within the latter. This book creates and analyses a 'community of records' to show that by reading both with and especially against the grain, it is probable that those responsible were radical right-wing nationalist extremists. Thus, for historical criminologists and crime investigators, the exploration of the sources examined could serve as a model of forensic analysis of cold cases. For those interested in the British Empire, the book shows how the British authorities had no real control over extremist nationalist politics and political violence in the 1930s no more than they did in the 1950s. For those with an interest in Cypriot history, this book will make startling and uncomfortable revelations about the so-called National Liberation Movement in Cyprus and suggest that the violence that gripped the island from the 1950s and led to partition could have been avoided